Latent classes of accounting outsourcing firms - Juntunen Jouni; Lepistö Sinikka; Juntunen Mari (Emerald, 2022)
Purpose
Outsourcing of accounting increasingly attracts research interest, but research concerning the impact of the benefits of outsourcing on firm capabilities and performance across firms remains limited. This paper aims to reveal the unobservable latent classes of firms that outsource their accounting functions by testing a research model concerning the topic.
Design/methodology/approach
The authors build on accounting outsourcing research and adapt a research model from the literature on business services outsourcing. The authors analyze the data from 261 small and medium-sized enterprises in Europe using finite mixture structural equation modeling (FMSEM) and additional methods.
Findings
The authors reveal three latent classes with different research models. Thriving outsourcers (N = 103) have a positive attitude toward accounting outsourcing and associate competitive capabilities with mediating the relationship from outsourcing benefits to firm performance. Annoyed outsourcers (N = 143) are dissatisfied with their accounting service provider and only associate outsourcing benefits with competitive capabilities. Convenient outsourcers (N = 15) feel comfortable with their current accounting service provider and associate outsourcing benefits with neither capabilities nor with firm performance.
Research limitations/implications
The study initiates the discussion about the unobservable heterogeneity among accounting outsourcers. The study introduces the use of the FMSEM method in accounting outsourcing research.
Practical implications
The study offers novel insights concerning accounting outsourcers and proposes original explanations for their outsourcing decisions that would help both the outsourcers and accounting service providers.
Originality/value
The study might be the first to categorize accounting outsourcers using FMSEM.